La burla como elemento de la comunicación en "Les liaisons dangereuses" - Mezcua Feria, Aurora; Ruiz Álvarez, Rafael (Estudios Humanísticos. Filología, 1986)
La burla como elemento de la comunicación en "Les liaisons dangereuses"